Short-term effects of stored homologous red blood cell transfusion on cardiorespiratory function and inflammation: an experimental study in a hypovolemia model - Biagini,S. (2018)
The pathophysiological mechanisms associated with the effects of red blood cell (RBC) transfusion on cardiopulmonary function and inflammation are unclear. We developed an experimental model of homologous 14-days stored RBC transfusion in hypovolemic swine to evaluate the short-term effects of transfusion on cardiopulmonary system and inflammation. Sixteen healthy male anesthetized swine (68±3.3 kg) were submitted to controlled hemorrhage (25% of blood volume). Two units of non-filtered RBC from each animal were stored under blood bank conditions for 14 days. After 30 min of hypovolemia, the control group (n=8) received an infusion of lactated Ringer's solution (three times the removed volume). The transfusion group (n=8) received two units of homologous 14-days stored RBC and lactated Ringer's solution in a volume that was three times the difference between blood removed and blood transfusion infused. Both groups were followed up for 6 h after resuscitation with collection of hemodynamic and respiratory data. Cytokines and RNA expression were measured in plasma and lung tissue. Stored RBC transfusion significantly increased mixed oxygen venous saturation and arterial oxygen content. Transfusion was not associated with alterations on pulmonary function. Pulmonary concentrations of cytokines were not different between groups. Gene expression for lung cytokines demonstrated a 2-fold increase in mRNA level for inducible nitric oxide synthase and a 0.5-fold decrease in mRNA content for IL-21 in the transfused group. Thus, stored homologous RBC transfusion in a hypovolemia model improved cardiovascular parameters but did not induce significant effects on microcirculation, pulmonary inflammation and respiratory function up to 6 h after transfusion.